PENGARUH TEKNIK MOZAIK TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK PRASEKOLAH DI WILAYAH KERJA PUSKESMAS KEMANTAN KABUPATEN KERINCI TAHUN 2024 - Silvia, Elwitri; Tyas, Dina Ayuning; Suganda, Yohana; Elfianti, Elfianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: According to the World Health Organization (2018: 382) the incidence of developmental delays in the United States is 12% to 16%, in Thailand 24% and in Argentina 22% and in Indonesia itself it ranges from 13% to 18%, there are developmental problems such as motor, language and behavioral delays, autism and hyperactivity increased. The purpose of the study was to determine the effect of mosaic techniques on fine motor development in preschool children in the Kemantan Health Center Work Area, Kerinci Regency in 2024., This study is a quantitative study with a Quasy-Experimental research design, namely with the One Group Pretest-Posttest design approach. The population in this study is The population in this study were all children with developmental delays as many as 17 people from January-June 2024 with a sample of 16 people. This research was conducted in the Kemantan Health Center Work Area. The research time was conducted in September 2024, The results of the study showed that on average most of the 9 (56.3%) respondents with fine motor development began to develop before being given the mosaic technique, on average most of the 12 (75.0%) respondents with fine motor development developed very well after being given the mosaic technique with a p value = 0.001 (p≤0.05), The conclusion of the study shows that there is an effect of the mosaic technique on fine motor development in preschool children in the Kemantan Health Center Work Area, Kerinci Regency in 2024. The researcher's suggestion from the research results is to be able to understand and apply it in daily midwifery practice in improving fine motor development in preschool children. Keywords: Mosaic Technique & Fine Motor Development